PERAN GENERASI Z DALAM PENGUATAN EKONOMI KREATIF - Ummi Khoiriyah; Isfandayani Isfandayani; Mas Deden Tirtajaya (DEVOSI, 2022)
Creative economy is a catch in thinking to get things that are economical. However, the contribution of Generation Z to the creative economy is still small, one of which is Generation Z in Sukarukun Village. This study aims to build the role of Generation Z in strengthening the creative economy. The implementation method in this activity uses the community education method by providing socialization, training and assistance to children and adolescents related to the creative economy which aims to increase public understanding and increase awareness of the importance of Generation Z's role in strengthening the creative economy. The results of this activity show that increasing insight related to the creative economy, Generation Z can make products about the creative economy by making handicrafts in the form of pencil cases that can be of economic value, designing product photos so that they are more attractive using photoroom applications, do product packaging and marketing on social media in the form of whatsapp business, instagram and tiktok.